2021
DOI: 10.3390/ijerph18136754
|View full text |Cite
|
Sign up to set email alerts
|

Mixed POT-BM Approach for Modeling Unhealthy Air Pollution Events

Abstract: This article proposes a novel data selection technique called the mixed peak-over-threshold–block-maxima (POT-BM) approach for modeling unhealthy air pollution events. The POT technique is employed to obtain a group of blocks containing data points satisfying extreme-event criteria that are greater than a particular threshold u. The selected groups are defined as POT blocks. In parallel with that, a declustering technique is used to overcome the problem of dependency behaviors that occurs among adjacent POT bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…In general, a high API indicates poor air quality [51]. Details regarding the calculation of API data can be referred to in Masseran and Safari [52] and Masseran [53]. This study investigates the data of an air pollutant index (API) series in Klang for the period of 1 January 2002 to 31 August 2020.…”
Section: Study Area and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In general, a high API indicates poor air quality [51]. Details regarding the calculation of API data can be referred to in Masseran and Safari [52] and Masseran [53]. This study investigates the data of an air pollutant index (API) series in Klang for the period of 1 January 2002 to 31 August 2020.…”
Section: Study Area and Datamentioning
confidence: 99%
“…In general, a high API indicates poor air quality [51]. Details regarding the calculation of API data can be referred to in Masseran and Safari [52] and Masseran [53].…”
Section: Study Area and Datamentioning
confidence: 99%
“…Based on each individual indices, their values can then be integrated based on the highest sub-indices to determine the API indices at particular times [45]. A detailed calculation on the standardization and determination of the sub-indices values for each pollutant variable can be referred to in Masseran and Safari [46]. Figure 2 illustrate the schematic process for determining the API value based on five pollutant variables [47].…”
Section: Study Area and Datamentioning
confidence: 99%
“…In [21], the Hierarchical-Generalized Pareto model is applied to API data from different locations to provide a precise estimation of the return levels for each location. Moreover, the mixed peak-overthreshold-block-maxima (POT-BM) approach was used to investigate the unhealthy events and showed that this approach has an excellent tradeoff between bias and variance in modeling the extreme events [22].…”
Section: Introductionmentioning
confidence: 99%